Efforts to Guidance and Counseling for the Drug Investigation Unit of the West Jakarta Metro Police in Suppressing the Number of Drug Abuse During the Corona Virus Disease-19 Pandemic - Bimo Satrio Rumekso (Advances in Police Science Research Journal, 2021)
The Covid-19 pandemic is one of the problems that has hit the world, including Indonesia since 2019. One of the impacts of this is the widespread circulation of drugs. To overcome these problems, the Drug Investigation Unit has duties in the repressive and preventive fields. In the preventive field, the Drug Investigation Unit provides guidance and counseling (Binluh) to the community and drug prisoners. This thesis aims to describe the description of drug crimes in West Jakarta during the Covid-19 pandemic, efforts to develop and educate the West Jakarta Metro Police Narcotics Investigation Unit in reducing the number of drug abuse during the Covid-19 pandemic, as well as the factors that influence the prevention of drug abuse cases. in West Jakarta during the Covid-19 pandemic. This research was made using a qualitative approach and the type of phenomenological research. The qualitative approach establishes research based on the overall social situation under study which includes aspects of places, actors, and activities that interact synergistically. The data will be analyzed through the stages of data collection, data reduction, data presentation, and the last is drawing conclusions. The theories used in this thesis are management theory, legal effectiveness, and crime prevention. The results of this study indicate that the implementation of guidance and counseling of the Narcotics Satres at the West Jakarta Police has not been carried out optimally. This happened because of the irregularity of the implementation of Binluh in accordance with the activity plan, the absence of a budget for conducting Binluh, and the absence of new breakthroughs in the implementation of Binluh. Efforts to optimize the implementation of Binluh are carrying out Binluh activities on a scheduled basis in accordance with the activity plans that have been made, submitting a budget for conducting Binluh in the following year to support the Binluh implementation process itself, and making a new breakthrough in the implementation of Binluh in order to find something new, innovative, and not monotonous.